Metastasis suppressor microRNA-335 targets the formin family of actin nucleators. - Jennifer Lynch; Maria H Meehan; John Crean; John Copeland; Raymond L Stallings; Isabella M Bray (PLoS ONE, 2013)
MiRNAs can have pleiotropic effects by targeting multiple genes belonging to diverse signalling networks. Alternatively, miRNAs can enhance the potency of their cellular effects by targeting multiple genes within the same genetic pathway. Previously, we and others have demonstrated that miR-335 is a potent suppressor of tumour cell migration, invasion and metastasis, in part by targeting several genes involved in these cellular processes, including ROCK1, MAPK1, LRG1, SP1 and SOX4. Here, we demonstrate that direct targeting of multiple members of the formin family of actin nucleators contributes to the inhibitory effects of miR-335 in neuroblastoma cells. We demonstrate that miR-335 regulates the expression of at least five formin family members and validate three family members, FMNL3, FMN2 and DAAM2, as direct targets of miR-335. The contribution of the formin family genes to cancer progression and metastasis has recently begun to emerge and here we demonstrate for the first time the ability of FMN2 and DAAM2 to regulate tumour cell migration and invasion, using siRNA-mediated inhibition of each of these formin genes. Finally, we demonstrate that the formin genes, in particular FMNL3, are responsible for the protrusion of actin-rich filopodia structures that contribute to the enhanced migratory and invasive potential associated with reduced expression of miR-335. Thus, direct targeting of the formin family contributes to the metastasis suppressing abilities of miR-335 by providing a direct regulatory link to the actin assembly machinery of the cell. We conclude that miR-335 is a master regulator of tumour cell migration and invasion by directly targeting a plethora of genes that effectively control cell migratory processes.